THE INFLUENCE OF COUNTRY IMAGE ON PRODUCT BRAND IN THE ROMANIAN SHOES INDUSTRY - PAȘTIU, Carmen Adina; MUREȘAN, Maria (Annales Universitatis Apulensis Series Oeconomica; Vol 2 No 16 (2014): Annales Universitatis Apulensis Series Oeconomica, 2014)
The current research study aims to analyze and identify the impact of the consumers’ perception on the brand image in the case of Romanian shoes products. The authors’ goal was that of shaping a multifactor model which underlies the consumers’ behavior on the brand image of a product. The study also provides top management strands of the Romanian light industry enterprises. The research is based on a study conducted in Romania shoes products. The quantitative research has been carried out using the online questionnaire consisting in: brand awareness, perceived quality, and brand loyalty dimensions. Analyzing the results of the present research there has been outlined a multifactor model showing the influence of the country image on shoes brands. The findings confirm the assumptions that the country's image has a crucial role on the consumer’s behavior in choosing different brands of shoes